2010
DOI: 10.1007/s10926-010-9257-1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Psychiatric Comorbidity on the Return to Work in Patients Undergoing Herniated Disc Surgery

Abstract: Identifying a high risk group for RTW and ATW at an early age is of utmost importance for the purpose of improving rehabilitation effects and to make a return to the work place easier. Specific interventions, such as social-medical counselling, pain therapy and management, as well as the assistance of mental health professionals during hospital and rehabilitation treatment are recommended for this risk group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
2
9
0
4
Order By: Relevance
“…Other studies confirmed the negative impact of presence of co-morbidity on work outcome [19][20][21][22]. Although in our study the presence of one co-morbid condition failed to reach significance, the trend is showing decreased odds on higher work ability.…”
Section: Discussionsupporting
confidence: 70%
“…Other studies confirmed the negative impact of presence of co-morbidity on work outcome [19][20][21][22]. Although in our study the presence of one co-morbid condition failed to reach significance, the trend is showing decreased odds on higher work ability.…”
Section: Discussionsupporting
confidence: 70%
“…Nguyen et al [5] note that only 26% of the patients who had surgery of lumbar spine returned to work, compared with 67% of the patients from a control group who had received conservative treatment. In a German study, Ziegler et al [6] note a high percentage of patients who returned to work. They studied 305 patients treated surgically for spinal disc disorder and considered the psychological and socio-economic burdens placed on the patients.…”
Section: Ijomeh 2013;26(3) 397mentioning
confidence: 98%
“…Three months after the operation, 84.5% of the patients were able to return to work. According to Ziegler et al [6], the factors that cause working activity disorders are lower-level education, unemployment, poor subjective job opportunities, long-term in-hospital treatment, prior spinal surgery, pain in other segments of the spine, as well as high intensity of subjectively-felt pain. According to the authors, the high-risk patients should receive a therapy that would involve medical, social, pain relief and psychological support.…”
Section: Ijomeh 2013;26(3) 397mentioning
confidence: 99%
“…Ein zentrales Ziel der Rehabilitation ist daher nicht nur die Vorbeugung des Fortschreitens einer chronischen Erkrankung sowie das ganze oder teilweise Beseitigen oder Kompensieren von Fähigkeitsverlusten oder -einschränkungen, sondern auch die Ermöglichung einer erfolgreichen Rückkehr in das Berufsleben [ 1 ] . Obwohl man davon ausgeht, dass Rückenoperationen mit einer höheren Frühberentungsrate assoziiert sind [ 7 -10 ] , gibt es bisher nur wenige Untersuchungen darüber, welche Einfl ussfaktoren die Rückkehr in das Erwerbsleben bei bandscheibenoperierten Patienten beeinfl ussen [ 11 ] . Unter anderem lassen sich hier Alter [ 12 ] , Berufsstatus [ 13 ] , negative Arbeitsfaktoren [ 13 ] , berufl iche Zufriedenheit [ 14 ] , berufsbedingte psychische Belastungen [ 13 ] sowie Schmerzen [ 12 , 14 , 15 ] …”
unclassified
“…Bisher gab es nur wenige Studien, die den Einfl uss psychischer Komorbidität auf die berufl iche Wiedereingliederung bei bandscheibenoperierten Patienten untersucht haben [ 11 ] . Zudem gibt es kaum Untersuchungen, deren Ergebnisse sich auf kategoriale Diagnosen psychischer Stö-rungen mittels standardisierter klinischer Interviews stützen.…”
unclassified